Tactical proficiency among table tennis players with and without intellectual disabilities - Van Biesen, D.; Mactavish, J.; Vanlandewijck, Y. (European Journal of Sport Science, 2014)
The effect of intellectual impairment on sports performance has received limited attention by researchers. As a contribution to closing this gap, the purpose of the present investigation was to examine the differences in tactical proficiency between table tennis players with and without intellectual disabilities (ID). These groups were matched for training-volume and experience and consisted of 41 male (age = 27±8) and 30 female (age= 28±8) elite players with ID and a reference group of 12 male (age= 24±12) and 5 female (age= 20±9) players without ID. In two different test settings - one a World Championship and the other a training camp - the players in each group performed 60 semi-standardised rallies against the same opponent. Players were told that 12 sets of five identical services would be delivered, and their goal was to return the service with the intention of `winning the point`. The test results were validated for this study, to compute tactical proficiency scores (maximal score of eight points) for each player. A two-way Analysis of Variance (ANOVA) revealed significantly lower proficiency scores for players with ID than for those without ID. Repeated-measures ANOVA revealed that within each series of five rallies, starting with identical services, all participants were able to significantly improve their tactical proficiency gradually, but players without ID scored 4.3±0.5 from the first ball on, and while athletes with ID only 3.3±0.7 after five balls. The results of this study indicate that ID is associated with decreased tactical proficiency in table tennis